2009
DOI: 10.1002/ccd.21768
|View full text |Cite
|
Sign up to set email alerts
|

Percutaneous closure of an iatrogenic atrial septal defect

Abstract: The use of the Tandem Heart percutaneous ventricular assist device (Tandem Heart pVAD, Cardiac Assist technologies, Pittsburgh, PA) as a bridge to recovery or to other cardiopulmonary support systems has been rising. One requirement for placement of this device is an intraatrial septostomy which is usually closed during the surgical insertion of more permanent ventricular assist devices. We present a case of a 62-year-old man with a residual acquired atrial septal defect (ASD) from Tandem Heart placement, whic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 11 publications
0
6
0
Order By: Relevance
“…There are multiple case reports of the deleterious effects of iASD (hypoxemia, heart failure, and systemic embolization). [8][9][10][11][12][13][14][15] There is only one single-center prospective study that suggested a possible negative impact of persistent iASD on right ventricular function, dyspnea, and mortality after TMVR Other studies have evaluated the effect of iASD on clinical outcomes, but were underpowered due to the very low incidence of adverse events (Table 1).…”
Section: Discussionmentioning
confidence: 99%
“…There are multiple case reports of the deleterious effects of iASD (hypoxemia, heart failure, and systemic embolization). [8][9][10][11][12][13][14][15] There is only one single-center prospective study that suggested a possible negative impact of persistent iASD on right ventricular function, dyspnea, and mortality after TMVR Other studies have evaluated the effect of iASD on clinical outcomes, but were underpowered due to the very low incidence of adverse events (Table 1).…”
Section: Discussionmentioning
confidence: 99%
“…There are a number of different procedures requiring TSP, including left‐sided cardiac ablations, percutaneous mitral valve repairs, mitral balloon valvulotomies, left atrial appendage closures, and certain ventricular assist device placements . In many cases, the tissue of the FO is punctured and manipulated with large size devices.…”
Section: Discussionmentioning
confidence: 99%
“…As mentioned above, there are various procedures that require a TSP including left‐sided cardiac ablation, percutaneous mitral valve repair, mitral balloon valvulotomy, left atrial appendage closure, and certain ventricular assist device placements . These procedures along with some newer and future procedures, including left ventricular endocardial pacing and percutaneous mitral and aortic valve implantation, could potentially bring about a greater prevalence of TSPs and thus higher incidences of potential complications .…”
Section: Introductionmentioning
confidence: 99%
“…More recently, LV mechanical support systems have been shown to precipitate right-to-left shunting and arterial hypoxemia in patients with heart failure with previously unrecognized ASD, patent foramen ovale, and iatrogenic/acquired defects. [18][19][20][21] The…”
Section: Atrial Septal Defect With a Right-to-left Shuntmentioning
confidence: 99%